ANXIETY, DEPRESSION AND STRESS IN NURSES DURING AND AFTER THE COVID-19 PANDEMIC: A look at the literature - Marques Mota, Hailany (2024)
During the Covid-19 pandemic, health professionals were faced with unexpected, demanding situations, facing various difficulties and as a result of this process they experienced an immensity of negative feelings. Among these professionals, nurses were faced with overload, which often led to stress due to their routines, as well as anxiety and depression. The objective of the present study was to collect data from the literature related to the topic on the occurrence of anxiety, depression and stress in nurses during and after the Covid-19 pandemic, as well as the risk factors associated with such occurrences. This is an integrative review of the literature whose search for materials took place in September 2023, on Google Scholar using the following key words: “covid” and “nurse” and “anxiety” and “depression” and “stress” and as a criterion For inclusion, works were prioritized: in the Portuguese language, in the time frame from 2020 to 2023 that had been carried out in the form of field research. 19 works were selected and analyzed. In their research, the authors reported occurrences of anxiety, depression and stress during and after Covid-19. In relation to the risk factors associated with the occurrence of these events, the following can be mentioned: fear, frustration, exhaustion, anguish, panic disorder, nervousness, concern about contaminating oneself and ending up contaminating the family, difficulties in decision-making, concern for the unknown among others.